Knowledge sharing maturity model for Jordanian construction sector. Issue 1 (16th January 2017) - Arif, Mohammed; Al Zubi, Mohammed; Gupta, Aman Deep; Egbu, Charles; Walton, Robert O.; Islam, Rubina
Abstract : Purpose: The purpose of this paper is to present a maturity model developed to assess knowledge sharing (KS) for the Jordanian construction sector. Design/methodology/approach: The research was conducted in three stages. The first stage consisted of the review of literature and documenting variables from the literature that highlight influence on KS in organizations. The second stage was designed for maturity model development by identifying the cultural factors that affect KS in the Jordanian construction sector through questionnaires and interviews. Factor analysis was used to find possible relationships between the cultural variables followed by semi-structured interviews. In the third stage the initial maturity model was refined through another set of semi-structured interviews. Findings: The model presented in the paper includes three levels of maturity. The first level identifies whether the variable barely exists in company's KS practices. The second level shows the occasional techniques which the company uses to increase KS activities. The final level demonstrates the importance of the variable in affecting KS as being fundamentally ingrained in the company's vision, mission, strategy and operations. Originality/value: The research has developed a model that can be used to measure the KS in an organization. Although the model has been applied to the construction industry, it can easily be modified to fit in the other sectors.